2021
DOI: 10.1021/acscatal.1c02443
|View full text |Cite
|
Sign up to set email alerts
|

Ceria-Based Materials for Thermocatalytic and Photocatalytic Organic Synthesis

Abstract: Value-added chemicals, fuels, and pharmaceuticals synthesized by organic transformation from raw materials via catalytic techniques have attracted enormous attention in the past few decades. Heterogeneous catalysts with high stability, long cycling life, good environmental-friendliness, and economic efficiency are greatly desired to accomplish the catalytic organic transformations. With the advantages of reversible Ce3+/Ce4+ redox pairs, tailorable oxygen vacancies, and surface acid–base properties, ceria-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(94 citation statements)
references
References 419 publications
2
81
0
Order By: Relevance
“…Imines as valuable intermediates are comprehensively applied in the fields of medicine and biology, in which the aerobic oxidative coupling of amines to generate corresponding imines has become a research hotspot. Compared with conventional thermocatalysis, photocatalysis as an environmentally friendly and cost-effective method has attracted widespread attention for chemical synthesis at room temperature. Up to now, a series of traditional semiconductors such as TiO 2 , CdS, and C 3 N 4 have been extensively explored for the visible-light-driven selective oxidation of amines to imines; however, their poor structure adjustment and low photocatalytic efficiency have limited their further applications in photocatalysis. Recently, emerging metal–organic frameworks (MOFs) with large surface areas and adjustable pores have attracted increasing attention as promising photocatalysts for organic synthesis because the metal-containing clusters in MOFs can act as semiconductor dots and the organic linkers as photoinduced electron initiators to complete the electron transfer via the linker to the metal cluster charge-transfer (LCCT) route. However, some intrinsic defects of MOFs, like poor visible-light adsorption and low stability as well as deficient efficiency of light utilization, have greatly restricted their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Imines as valuable intermediates are comprehensively applied in the fields of medicine and biology, in which the aerobic oxidative coupling of amines to generate corresponding imines has become a research hotspot. Compared with conventional thermocatalysis, photocatalysis as an environmentally friendly and cost-effective method has attracted widespread attention for chemical synthesis at room temperature. Up to now, a series of traditional semiconductors such as TiO 2 , CdS, and C 3 N 4 have been extensively explored for the visible-light-driven selective oxidation of amines to imines; however, their poor structure adjustment and low photocatalytic efficiency have limited their further applications in photocatalysis. Recently, emerging metal–organic frameworks (MOFs) with large surface areas and adjustable pores have attracted increasing attention as promising photocatalysts for organic synthesis because the metal-containing clusters in MOFs can act as semiconductor dots and the organic linkers as photoinduced electron initiators to complete the electron transfer via the linker to the metal cluster charge-transfer (LCCT) route. However, some intrinsic defects of MOFs, like poor visible-light adsorption and low stability as well as deficient efficiency of light utilization, have greatly restricted their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the advantages of reversible Ce 3+ /Ce 4+ redox pairs, tailorable oxygen vacancies, and surface acid−base properties, ceria-based catalysts are actively investigated in the fields of catalytic organic synthesis [135]. This is the reason why, in recent years, several reviews on special organic reactions over CeO 2 -based catalysts were reported, such as transformations of nitriles and amides [136], CO 2 conversion with alcohols or amines [137,138]; sustainable oxidation processes [139] and transformations of biomass, its derivatives, and downstream chemicals [140].…”
Section: Ceriamentioning
confidence: 99%
“…In recent years, upcycling catalytic methods for plastics conversion, such as thermocatalytic and photocatalytic routes, have received increasing attention because the plastic waste can be upgraded into valuable fuels, chemicals, or materials with additional economic benefits. [30][31][32][33][34][35][36] Compared to the thermochemical route, including pyrolysis and gasification, which generally require large energy inputs and harsh reaction conditions such as high temperature and pressure, photocatalysis is considered as a greener and cheaper technique owing to its mild conditions of ambient pressure and temperature using sunlight or artificial light (e.g., LEDs with low-energy consumption) as the energy source. [37][38][39][40][41][42] Furthermore, in contrast with the severe conditions applied during thermocatalysis, the mild process of photocatalysis has great potential for the precise activation of specific chemical bonds with other functional groups preserved, which can achieve high selectivity toward targeted products.…”
Section: Introductionmentioning
confidence: 99%